Juvenile Hormone Studies in Drosophila melanogaster - Zhang, Xiaoshuai; Li, Sheng; Liu, Suning (Frontiers in Physiology, 2022)
In the field of insect endocrinology, juvenile hormone (JH) is one of most wondrous entomological terms. As a unique sesquiterpenoid hormone produced and released by the endocrine gland, corpus allatum, JH is a critical regulator in multiple developmental and physiological processes, including metamorphosis, reproduction, and behavior. Benefitted from the precise genetic interventions and simplicity, the fruit fly, Drosophila melanogaster, is an indispensable model in JH studies. This review aims to present the regulatory factors on JH biosynthesis, and an overview of the regulatory roles of JH in Drosophila. The future directions of JH studies are also discussed, and a few hot spots are highlighted.